OPERATION EARTHQUAKE 2011: CHRISTCHURCH EARTHQUAKE DISASTER VICTIM IDENTIFICATION. - Trengrove, H. (J Forensic Odontostomatol, 2011)
At 12.51pm on Tuesday 22 February 2011, an earthquake of magnitude 6.3 struck the Christchurch region of New Zealand causing massive destruction with hundreds of people injured and killed. The New Zealand Society of Forensic Odontology response commenced two hours after the earthquake with the implementation of the national Disaster Victim Identification (DVI) forensic odontology plan. The importance of good planning, the integration of odontology as part of the immediate response and the deployment of odontology personnel to the scene were features of this operation. Stringent quality assurance processes were integrated into the planning which assisted in the robust outcomes. Smile photograph comparisons played a role in a number of difficult identifications. In the four months following the earthquake teams of odontology personnel worked tirelessly in an effort to identify the remains of those killed during the disaster. At the conclusion of the operation 97% of the deceased have been identified and returned to their families.